Nurse‐Family Partnership nurses' attitudes and confidence in identifying and responding to intimate partner violence: An explanatory sequential mixed methods evaluation. (20th July 2021) - Jack, Susan M.; Kimber, Melissa; Davidov, Danielle; Ford‐Gilboe, Marilyn; Wathen, C. Nadine; McKee, Christine; Tanaka, Masako; Boyle, Michael; Johnston, Carolyn; Coben, Jeffrey; Gasbarro, Mariarosa; McNaughton, Diane; et al.
Abstract: Aims: To evaluate the effect of an intimate partner violence intervention education component on nurses' attitudes in addressing intimate partner violence; complementary aims included understanding nurses' perceptions of the education and how it influenced their attitudes and confidence to address intimate partner violence in practice. Design: An explanatory sequential mixed methods design embedded within a 15‐site cluster randomized clinical trial that evaluated an intimate partner violence intervention within the Nurse‐Family Partnership programme. Methods: Data were collected between February 2011 and September 2016. Quantitative assessment of nurses' attitudes about addressing intimate partner violence was completed by nurses in the intervention ( n  = 77) and control groups ( n  = 101) at baseline, 12 months and at study closure using the Public Health Nurses' Responses to Women Who Are Abused Scale. Qualitative data were collected from nurses in the intervention group at two timepoints ( n  = 14 focus groups) and focused on their perceptions of the education component. Data were analysed using content analysis. Results: Nurses in the intervention group reported large improvements in their thoughts, feelings and perceived behaviours related to addressing intimate partner violence; a strong effect of the education was found from baseline to 12 months and baseline to study closure timepoints. Nurses reported that the education component was acceptable and increased their confidence to address intimate partner violence. Conclusion: Nurses reported improved attitudes about and confidence in addressing intimate partner violence after receiving the education component. However, these findings need to be considered together with trial results showing no main effects for clients, and a low level of intervention fidelity. Impact: These evaluation findings underscore that improvement in nurses' self‐reported educational outcomes about addressing intimate partner violence cannot be assumed to result in adherence to intervention implementation or improvement in client outcomes. These are important considerations for developing nurse education on intimate partner violence.